Pregnancy Wastage Due to Fetal Congenital Malformations - Sangwan, Vijayata; Khandelwal, Shivani; Mahendru, Rajiv; Lakra, Pinkey; Siwach, Sunita (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVES: To study the pattern of various congenital anomalies in rural Haryana. STUDY DESIGN: This was a retrospective study conducted over 1 and ½ years (from January 2015 to June 2016) in a tertiary care center in Haryana, India. RESULTS: Out of 11,178 births, 227 babies had gross congenital malformations 2.03%. In literature, the most common birth defect reported in western countries is cardiovascular anomalies while in India and eastern countries, it’s the neural tube defect. In our study also, neural tube defects were the most common congenital anomalies accounting for 64.31% of total anomalies. They were more common in unbooked patients (70%) and the rural population. So, the main cause appears to be a lack of awareness and illiteracy. CONCLUSION: There is a need for increased awareness and folic acid supplementation routinely in the periconceptional period to decrease the incidence of congenital anomalies.